Glucose excursions and hypoglycemia in patients with type 2 diabetes treated with mitiglinide/voglibose versus glimepiride: A randomized cross‐over trial1: 在使用米格列奈/伏格列波糖或格列美脲治疗的2型糖尿病患者中评估血糖波动与低血糖:一项随机交叉试验. Issue 8 (11th April 2018) - Fujimoto, Kanta; Shibayama, Yui; Yamaguchi, Eriko; Honjo, Sachiko; Hamasaki, Akihiro; Hamamoto, Yoshiyuki
Abstract: Background: Glucose excursions and hypoglycemia are associated with cardiovascular complications. However, no studies have evaluated glucose excursions and the frequency of hypoglycemia in patients treated with mitiglinide/voglibose versus glimepiride as add‐on to dipeptidyl peptidase‐4 inhibitor therapy. Methods: This cross‐over trial included 20 patients with type 2 diabetes. After initiating vildagliptin 100 mg, patients were randomly assigned to receive mitiglinide 10 mg/voglibose 0.2 mg three times daily for 3 days followed by glimepiride 1 mg once daily for the subsequent 3 days as add‐on therapy, or vice versa. Glucose excursions and hypoglycemia frequency were measured using 24‐h continuous glucose monitoring. Metabolic profile changes were evaluated using a meal tolerance test. Results: The mean glucose levels in the mitiglinide/voglibose and glimepiride phases were identical (8.01 vs 8.24 mmol/L, respectively). However, during the mitiglinide/voglibose phase compared with the glimepiride phase, the standard deviation of glucose (1.30 vs 2.10 mmol/L; P < 0.001), mean amplitude of glycemic excursions (3.47 vs 5.28 mmol/L; P < 0.001), M‐value (24.6 vs 70.0; P < 0.001), continuous overlapping net glycemic action for a 1‐h time interval (22.6 vs 31.0; P < 0.001), and area under the curve >10 mmol/L (0.18 vs 0.52 mmol/L per h; P < 0.001) were significantly lower. Hypoglycemia (glucose <3.8 mmol/L) was not observed during the mitiglinide/voglibose phase, but occurred 0.35 times/day in those taking glimepiride. Moreover, the mitiglinide/voglibose phase had higher premeal and lower post‐meal glucose levels than the glimepiride phase. Conclusions: Adding mitiglinide/voglibose to vildagliptin therapy results in more efficient postprandial glucose control and less hypoglycemia than adding glimepiride. Abstract : Highlights This is the first randomized cross‐over trial using continuous glucose monitoring to compare glucose excursions and hypoglycemia frequency in patients with type 2 diabetes treated with mitiglinide/voglibose versus glimepiride as add‐on to the dipeptidyl peptidase‐4 (DPP‐4) inhibitor. The mean glucose levels in the mitiglinide/voglibose and glimepiride phases were identical, but fewer glucose excursions and no episodes of hypoglycemia were observed with mitiglinide/voglibose. Mitiglinide/voglibose as an add‐on to a DPP‐4 inhibitor may be a suitable therapeutic option for preventing cardiovascular events.